Implications of Linking National Emission Trading Schemes prior to the Start of the First Commitment Period of the Kyoto Protocol - Sven Bode (Hamburg Institute of International Economics (HWWA), 2003)
After greenhouse gas emission trading on country level had been proposed by the Kyoto Protocol agreed on in 1997, a discussion on the introduction of national schemes with entities as participants ensued. This discussion also raised the question if and how such systems can be linked. We first discuss this issue with regard to technical feasibility and environmental integrity. We find that linking is generally not prevented due to technical reasons. Environmental integrity may, however, be endangered depending on the specific designs of the schemes to be linked. We then analyse the economic impact of linking national schemes. Even though linking national schemes can increase overall cost-efficiency this picture changes if systems are linked prior to the start of the first Kyoto commitment period. Seller and buyer may have different interests with regard to linkage and the transfer of AAUs (= emission rights under the Protocol). Voluntarily linking can thus not be expected. In case that the linkage is prescribed by super-national organisations as for example the EU commission, both winners and losers are likely to be produced. This in turn may refrain member states from approving such approaches.
Keywords: Q28; Q25; 330; Klimaschutz; Umweltzertifikat; Nationalstaat; Internationale wirtschaftspolitische Koordination; Kosten-Nutzen-Analyse; Theorie